Breaking the Glass Ceiling? The Effect of Board Quotas on Female Labor Market Outcomes in Norway - Marianne Bertrand; Sandra E. Black; Sissel Jensen; Adriana Lleras-Muney (Institute for the Study of Labor (IZA), 2014)
In late 2003, Norway passed a law mandating 40 percent representation of each gender on the board of publicly limited liability companies. The primary objective of this reform was to increase the representation of women in top positions in the corporate sector and decrease gender disparity in earnings within that sector. We document that the newly (post-reform) appointed female board members were observably more qualified than their female predecessors, and that the gender gap in earnings within boards fell substantially. While the reform may have improved the representation of female employees at the very top of the earnings distribution (top 5 highest earners) within firms that were mandated to increase female participation on their board, there is no evidence that these gains at the very top trickled-down. Moreover the reform had no obvious impact on highly qualified women whose qualifications mirror those of board members but who were not appointed to boards. We observe no statistically significant change in the gender wage gaps or in female representation in top positions, although standard errors are large enough that we cannot rule economically meaningful gains. Finally, there is little evidence that the reform affected the decisions of women more generally; it was not accompanied by any change in female enrollment in business education programs, or a convergence in earnings trajectories between recent male and female graduates of such programs. While young women preparing for a career in business report being aware of the reform and expect their earnings and promotion chances to benefit from it, the reform did not affect their fertility and marital plans. Overall, in the short run the reform had very little discernable impact on women in business beyond its direct effect on the newly appointed female board members.
Keywords: J1; J3; 330; gender discrimination; board of directors